(untitled) (African Journal of Fisheries Science, 2014)
A one month trial of sex reversal treatment of O. niloticus fry of varying stocking densities was performed in hapas-in-pond to determine the growth performance characteristics and profitability. Larvae were selected, collected, weighed and stocked inside a 10.0 m2 hapas in a 0.2 ha pond with stocking densities of 10000 (A), 15000 (B) and 20000 (C). Each stocking were made in triplicate. Fry were fed with a 36% crude protein plus hormone incorporated feed five times a day. Weekly samplings of fry were done including water quality parameters. Final average body weights of treated fry were 0.226 ± 0.02, 0.125 ± 0.02 and 0.080 ± 0.01 g for treatments ‘A’, ‘B’, and ‘C’ stocks respectively. The fry growth in treatment ‘A’ was significant (at p < 0.05) among all other stocks. It also exhibited high specific growth rate and a lower feed conversion rate than others; however, high survival was achieved with fry in treatment ‘B’. High value of fry crop was achieved in treatment ‘C’ with a value of GH¢ 638.96. Although profit index did not vary significantly from each other, the treatment ‘B’ reached the highest value of 23.13 ± 9.01. The increasing fry stocking density of fry significantly affected the growth and feeding conversion rate, however, it did not affect the survival data. Due to the high profit index, relatively high growth rate and high survival, treatment ‘B’ is recommended for fry rearing in a 10.0 m2 hapa-in pond system.